Conversation Analysis of Turn Taking in the Political Interview between Luara Kuenssberg and Boris Johnson - Hasson, Sattar Mutar; Ahmed, Musleh Shweesh (Al-Adab Journal, 2022)
The concentrate on political interview between Luara Kuenssberg and Boris Johnson. According to the researcher’s knowledge a lot of interviews have been studied pragmatically, but no one has tackled them in a conversation analysis study. So, this field needs research because it is one of the scientific fields that was not previously studied. The study aims at 1- examining the dominant of the turn taking system between the participants in the interview. 2- The analysis is focused on the utterances said by speakers of the dialogue between Luara Kuenssberg and Boris Johnson. The study hypothesizes that 1- the textual structure of interview is organized in accordance with feature of the turn-taking system. 2- turn taking system dominants the participants in their interview. To achieve the aims of the present study and to validate its hypotheses, one script of political interviews is selected. The theoretical model used as the basis for the analytical work is a synthesis of theoretical views and practical procedures proposed and used by Sacks, H, Schegloff, E, and Jefferson, G, (1978). The present study employed a descriptive qualitative approach since the findings were presented in narrative or textual descriptions. The conclusions of the analysis confirm the two hypotheses of the present study. They are as follows :1- Structures of interviews are organized in accordance with specific features operating on the turn-taking system. Turn allocation process is controlled by the interviewer who is considered the main controller of the conversation. 2- Interviewers alone can maintain their turns by continuous speech causing temporal overlap in the display of turns.